Towards people-centric smart city development: Investigating the citizens’ preferences and perceptions about smart-city services in Taiwan - Ji, Tingting; Chen, Jieh-Haur; Wei, Hsi-Hsien; Su, Yu-Ching (Sustainable cities and society, 2021)
•Investigate citizens’ preferences and perceptions about smart city (SC) services.•Most citizens acknowledge that SC services contribute to human needs.•Citizens slightly prefer hard-domain services over the soft ones.•Provide suggestions for informing people-centric SC development. City administrators hoping to achieve people-centric smart city (SC) development require a clear understanding of citizens’ preferences and perceptions about SC services. This study fills that need by presenting evidence-based research on such preferences and perceptions from the perspective of need theories, taking Taiwan as a case study. Specifically, we investigated Taiwanese citizens’ preferences for 35 SC services of seven dimensions classified in two domains, as well as their three perceptions of the usefulness of these SC services in the realization of human needs. The results show that most of our respondents clearly perceived SC services as both important and useful to their existence, relatedness, and growth needs, and that they expressed relatively higher preferences for such services to operate in the “hard” domain – e.g., smart energy, smart transport, or smart safety –than the “soft” one, e.g., smart living. Based on these findings, this study provides policy recommendations that, if implemented, could be expected to advance SC development by increasing citizens’ usage of SC services in both the hard and soft domains, and serve the wider aim of improving their well-being and quality of life.